1969
DOI: 10.1136/jcp.22.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal fluid enzyme patterns in benign and malignant lesions of the female genital tract

Abstract: SYNOPSISThe enzymes phosphohexose isomerase, lactate dehydrogenase, hydroxybutyrate dehydrogenase, isocitric dehydrogenase, glutamate dehydrogenase, and sorbital dehydrogenase were assayed in cases of known carcinoma of the cervix and of carcinoma in situ. Phosphohexose isomerase, lactate dehydrogenase, and isocitric dehydrogenase were also assayed in a number of normal women and in those with benign lesions. It is unlikely that vaginal fluid enzymology will provide a screening test for cervical carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1971
1971
1981
1981

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The overall increase in aspirate lactate dehydrogenase activity found among patients with carcinoma in situ (Group A ) over normal patients (Emes et al, 1980) and the further increase with the appearance of clinically invasive carcinomas (Group B) (Table I) is in general agreement with results obtained elsewhere for lactate dehydrogenase and other glycolytic enzymes in vaginal fluid (Lawson and Watkins, 1965;Muir, 1966;Boyd et al, 1967;Stagg and Whyley, 1968;Muir and Valteris, 1969). Among postmenopausal women, any increase in enzyme activity occurring with the appearance of carcinoma in situ was masked by the normal postmenopausal increase in enzyme activity.…”
Section: Discwssionsupporting
confidence: 87%
See 3 more Smart Citations
“…The overall increase in aspirate lactate dehydrogenase activity found among patients with carcinoma in situ (Group A ) over normal patients (Emes et al, 1980) and the further increase with the appearance of clinically invasive carcinomas (Group B) (Table I) is in general agreement with results obtained elsewhere for lactate dehydrogenase and other glycolytic enzymes in vaginal fluid (Lawson and Watkins, 1965;Muir, 1966;Boyd et al, 1967;Stagg and Whyley, 1968;Muir and Valteris, 1969). Among postmenopausal women, any increase in enzyme activity occurring with the appearance of carcinoma in situ was masked by the normal postmenopausal increase in enzyme activity.…”
Section: Discwssionsupporting
confidence: 87%
“…It is of interest that the presence of symptoms suggestive of pelvic disease did not appear to increase aspirate lactate dehydrogenase activity. Other studies have indicated that a raised aspirate enzyme activity may be the result of an inflammatory response (Muir and Valteris, 1969) and, in biopsy material, enzyme levels are increased in certain benign conditions such as chronic cervicitis (Mainigi, 1972), cervical erosion and atrophic vaginitis (Bell and Egerton, 1965).…”
Section: Eflect Of Initial Histology On Lactate Dehydrogenase Activitmentioning
confidence: 99%
See 2 more Smart Citations